OPTIMALISASI PRODUKSI USAHATANI PEPAYA (Carica papaya L.) DI KELURAHAN PALAS KECAMATAN RUMBAI KOTA PEKANBARU - Mardhan, Randi; Tety, Ermi; Tarumun, Suardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research purpose is: 1) to analyze the farm of production of papaya california and papaya bangkok. 2) toanalyze the optimal allocation of resources owned by farmers of papaya california and papaya bangkok to achieve optimal condition in the Palas Village Rumbai District of Pekanbaru. The research was conducted in the Palas Village Rumbai District of Pekanbaru, the reserch was conducted approximately for 4 months with the survey method, the sample was taken as many as 32 samples by using purposive sampling method. the model of analysis that will be used in this research is to obtain the optimal combination of production rate by using Linear Programming models using QM for Windows version 1.3 to papaya california and papaya bangkok farm. From the research results of optimization analysis showing that the combination of production for papaya california and papaya bangkok is by planting 4.2065 Ha for papaya california and 2.5508 Ha for papaya bangkok. In the analysis of optimal resource that includes an active constraint is the availability of capital constraints and cost constraints of seeds which means if farmers increase the number of resource availability constraints, it will increase the rate of profit. While the other constraints, constraints of availability of land, labor costs constraints, fertilizers cost constraints, and pesticides cost constraints into passive constraints or excessive which means the availability of unused resources as a whole.   Keywords: Optimization, Production, Profits, Papaya